Um mecanismo de reputação para redes veiculares tolerantes a atrasos e desconexões - Wellington Passos de Paula (2009)
Vehicular Ad Hoc Networks (VANETs) constitute a new paradigm on mobile computing with many potential applications. Among the possibilities, we can highlight security applications in which network users can exchange information about the traffic conditions and the occurrence of risk events in the roads such as the oil accumulation in determined point of a track. However, in cooperative scenarios like those, there is always the risk of user's behavior be conditioned by their personal objectives instead of the general interest. Because of this, serious accidents may happen once wrong information can be used in the decision process executed by the vehicles. Therefore, the development of security mechanisms is necessary to validate data's reliability received by network participants. This work presents a reputation mechanism for VANETs, called RMDTV (Reputation Mechanism for Delay Tolerant Vehicular Networks). Through this mechanism, network members qualify other members responsible for sending correct information. The emitted qualifications are sent towards their destiny by the network. However, as the VANET's vehicles can be exposed to total connectionless moments, caused, for example, by their high mobility, we have chosen the Delay Tolerant Networks (DTNs) concepts to support such situations. Once received, they are added to all generated messages by their carriers in intention of attesting their reliability. Thus, network users can previously verify the new neighbors' reliability, even before data is exchanged. Simulation results show that RMDTV considerably increases the quality of taken decisions by members of a VANET exchanging information about the traffic conditions on the road, even in the presence of a great amount of malicious nodes